High performance biological methanation in a thermophilic anaerobic trickle bed reactor. (December 2017) - Strübing, Dietmar; Huber, Bettina; Lebuhn, Michael; Drewes, Jörg E.; Koch, Konrad
Highlights: Thermophilic trickle bed reactor as a promising concept for biological methanation. Productivity of 15.4 m 3 CH4 /(m 3 ·d) with 98% CH4 in a non-pressurized reactor. Significant impact of metabolic water production during dynamic operation. pH and nutrient control are crucial for stable process performance. Rapid adaption of mesophilic inoculum to thermophilic conditions after start-up. Abstract: In order to enhance energy efficiency of biological methanation of CO2 and H2, this study investigated the performance of a thermophilic (55 °C) anaerobic trickle bed reactor (ATBR) (58.1 L) at ambient pressure. With a methane production rate of up to 15.4 m 3 CH4 /(m 3 trickle bed ·d) at methane concentrations above 98%, the ATBR can easily compete with the performance of other mixed culture methanation reactors. Control of pH and nutrient supply turned out to be crucial for stable operation and was affected significantly by dilution due to metabolic water production, especially during demand-orientated operation. Considering practical applications, inoculation with digested sludge, containing a diverse biocenosis, showed high adaptive capacity due to intrinsic biological diversity. However, no macroscopic biofilm formation was observed at thermophilic conditions even after 313 days of operation. The applied approach illustrates the high potential of thermophilic ATBRs as a very efficient energy conversion and storage technology.